An Analysis of the Translanguaging Practice In Maudy Ayunda’s Youtube Channel - Amanda, Si Luh Nyoman Julia Tria; Mahayanti, Ni Wayan Surya; Budiarta, Luh Gede Rahayu (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The practice of translanguaging still raises confusion as to whether it is similar to other linguistic practices. We realize that individuals who have the ability to master more than one language will consciously and spontaneously exchange or mix languages in a particular social action. The mindset of monolingualism is often a limitation for speakers of bilingualism or multilingualism to use all the language resources they have to form a meaning. This study aims to look at the translanguaging practices that appear in vlog videos belonging to public figures such as Maudy Ayunda and see how the audience reacts in the comment section of Maudy Ayunda's personal YouTube channel. Because previous research is more focusing on implementing the translanguaging practice into the classroom and searching for teacher or student perception towards translanguaging. This research employs a case study qualitative research approach and thematic analysis to examine the themes that emerge from the video transcripts and comments. The findings of this study found that Maudy Ayunda frequently speaks entirely in English to convey feelings of enthusiasm. And the research findings also discovered varied reactions in the comment section